Baffling efficiency insights gained from tracer studies at 32 Washington treatment plants. Issue 1 (28th December 2018) - Porter, Russell L.; Stewart, Keith P.; Feagin, Nancy; Perry, Sam
Abstract : This article summarizes tracer studies performed at 32 water treatment plants in Washington State ranging from 5 to 5, 400 gpm, with contact basins from 200 gal to 1.5 mil gal. Multiple tracer studies were performed at each plant. The goal of the tracer studies was to determine the baffling efficiency (BE) of each basin by determining T10 /T, where T10 is the time at which 10% of a tracer is measured at the outlet of a basin, and T is the hydraulic residence time. The tracer studies indicated that most facilities historically used BE values higher than what the tracer studies indicated for calculating compliance with disinfection regulations. The majority of the basins were rectangular, baffled basins. The tracer studies indicated that standard design parameters, such as length‐to‐width ratio, were not as accurate in predicting basin performance compared with calculating baffled channel cross‐sectional velocity. This effect was pronounced where cross‐sectional flow velocity was below the Reynolds laminar flow threshold. For circular, baffled basins, a relationship between cross‐sectional velocity and BE was also evident. The study also identified issues with plants having parallel, chlorine contact basins where uneven flow splitting between basins created an overall system BE less than the BE of individual basins.